Coupled analysis of mechanical- and corrosion-related degradation of carbon steel spent fuel container. (September 2014) - King, F.; Burt, D.; Ganeshalingam, J.; Gardner, P.; Sanderson, D.; Watson, S.; Padovani, C.
<x content-type="archive" xml:space="preserve">Abstract</x> Failure of high level waste/spent fuel containers is most likely to occur as a result of mechanical overload following a period of corrosion that results in a reduction of the wall thickness and/or the degradation of the material properties. There can be significant interaction between the mechanical loads and the corrosion processes to which a disposal container is subjected which, in turn, can influence the mode and time of failure. Here, these interactions are illustrated for a single shell, carbon steel spent fuel container during its entire life cycle, from the time of manufacture through to the long term behaviour in a bentonite backfilled geological disposal facility. The evolution of the structural integrity of the container is illustrated through the use of failure assessment diagrams.